2004
DOI: 10.1097/01.ju.0000138187.56050.20
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Partial Nephrectomy: Effect of Warm Ischemia on Serum Creatinine

Abstract: Based on postoperative serum creatinine warm ischemia time up to 55 minutes does not significantly influence long-term renal function after LPN. Thus, during LPN efforts to minimize warm ischemia are important but they should not jeopardize cancer control, hemostasis or collecting system closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 16 publications
1
81
0
2
Order By: Relevance
“…While some studies have found that the impact of shortterm warm ischemia upon postoperative renal function is negligible, 5,6 and compares favorably to total loss of the renal unit by radical nephrectomy, 7 it is possible that the renal reserve provided by a normal contralateral kidney may mask the loss of renal function to a considerable degree. Indeed, studies evaluating functional outcomes of partial nephrectomy in the setting of a solitary kidney favor the open approach, as cold ischemia and shorter overall ischemic times appear to provide superior preservation of functional renal reserve.…”
mentioning
confidence: 99%
“…While some studies have found that the impact of shortterm warm ischemia upon postoperative renal function is negligible, 5,6 and compares favorably to total loss of the renal unit by radical nephrectomy, 7 it is possible that the renal reserve provided by a normal contralateral kidney may mask the loss of renal function to a considerable degree. Indeed, studies evaluating functional outcomes of partial nephrectomy in the setting of a solitary kidney favor the open approach, as cold ischemia and shorter overall ischemic times appear to provide superior preservation of functional renal reserve.…”
mentioning
confidence: 99%
“…18,19 Moreover, in retrospective studies, the warm ischemia of 40 to 55 minutes was safe and sufficient for the complete recovery of renal function. 20,21 Lee and colleagues demonstrated that ultimate renal function decreases proportionally with increasing ischemia time in the warm and cold ischemia groups. 22 Accordingly, we believe that our results provide information on the correlation between the anatomical features of renal tumours and the functional outcomes of RAPN.…”
Section: Discussionmentioning
confidence: 99%
“…The "safe" window of warm ischemia time is unknown despite several studies assessing its impact. [10][11][12][13] In this series none of the patients had preoperative baseline creatinine Ͼ2.0 mg/dL, so clearly the population was somewhat selected for tolerance of ischemia. Importantly, however, warm ischemia times were relatively short.…”
Section: Discussionmentioning
confidence: 99%